The untapped potential of seascape genomics in the North Pacific - Timm, Laura E.; Tucker, Nicholas; Rix, Anna; LaBua, Savannah; López, J. Andrés; Boswell, Kevin M; Glass, Jessica R (Frontiers in Conservation Science, 2023)
Seascape genomics provides a powerful framework to evaluate the presence and strength of environmental pressures on marine organisms, as well as to forecast long term species stability under various perturbations. In the highly productive North Pacific, forage fishes, key trophic links across ecosystems, are also contending with a rapidly warming climate and a litany of associated oceanographic changes (e.g., changes in salinity, dissolved oxygen, pH, primary production, etc). These changes can place substantial selective pressures on populations over space and time. While several population genomics studies have targeted forage fishes in the North Pacific, none have formally analyzed the interactions between genotype and environment. However, when population genomics studies provide collection location information and other critical data, it is possible to supplement a published genomic dataset with environmental data from existing public databases and perform "post hoc seascape genomics" analyses. In reviewing the literature, we find pertinent metadata (dates and locations of sample collection) are rarely provided. We identify specific factors that may impede the application of seascape genomics methods in the North Pacific. Finally, we present an approach for supplementing data in a reproducible way to allow for post hoc seascape genomics analysis, in instances when metadata are reported. Overall, our goal is to demonstratevia literature reviewthe utility and importance of seascape genomics to understanding the long term health of forage fish species in the North Pacific.